Dating and romantic relationships of adolescents with intellectual and developmental disabilities. (31st December 2019) - Heifetz, Marina; Lake, Johanna; Weiss, Jonathan; Isaacs, Barry; Connolly, Jennifer
ABSTRACT: Introduction: Adolescents with intellectual and/or developmental disabilities (IDD) are at high risk for sexual exploitation, yet there is a paucity of research on their romantic relationships. The objectives of this study were to examine the romantic understanding and experiences of youth with IDD. Methods: Thirty‐one adolescents (16–19 years; 21 males and 10 females) with IDD (12 participants with additional diagnosis of ASD) were recruited from a community health clinic. Individual interviews and questionnaires assessed cross‐sectionally these youths': (1) romantic conceptualizations; (2) romantic awareness (knowledge of: romantic relationships, sexual behaviours, initiating relationships); (3) involvement; (4) social competence; and (5) expectations for autonomy. Parent perspectives on these topics were also captured through questionnaires. Results: While 85% reported an immediate desire for a romantic relationship, only 35% were currently in a relationship. Qualitative findings indicated that 14% of youth were unable to differentiate between a romantic relationship and a friendship. Among those who could make this distinction, romantic relationships were conceptualized as serious, commitment for life, and primarily for companionship. Adolescents with ASD, compared to those without ASD, showed weaker social competence and lower romantic awareness. Parents were adolescents' primary source of information about relationships. Finally, parents and adolescents differed in their perception of the age at which they were ready to date. Conclusions: This study contributes to our understanding of the romantic experiences of youth with IDD. Prevention efforts focused on education may be important to help ensure these youth develop safe and healthy relationships.